The Influence of Iodide and Starch Concentration into I2-Starch Complex Formationfor Determination of Iodate Spectrophotometrically - Eka Ratri Noor Wulandari (Program Pendidikan Vokasi Universitas Brawijaya, 2016)
Iodine is a substance that is important and required by human body which is usually found in table salt. Generally,the species that exist in salt ispotassium iodate (KIO3). This research was conducted to analyze iodate content using spectrophotometric method based on the formation of blueiodine-starch complex. The influential parameters in analysis were concentration of iodide and starch concentration. Iodide was used as reducing agent to reduce the iodate while starch was used as a complexing reagent that would form a complex with I2 which produced a blue color. The method showed optimum results at22.85 x 10-4M of iodide concentration and 1% of starch concentration at the maximum wavelength of 611 nm.